2005
DOI: 10.1051/0004-6361:200400129
|View full text |Cite
|
Sign up to set email alerts
|

The ionization structure of early-B supergiant winds

Abstract: Abstract. We present empirically determined ionization conditions for the winds of 106 luminous B0 to B5 stars observed by IUE. The UV wind lines are modelled to extract products of mass-loss rates times ionization fractions (Ṁ q i (w), where w = v/v ∞ ) for N , C , Si , Si , Al  and C . We describe the general behaviour of theṀ q i (w) and their ratios, demonstrating that the wind ionization increases with distance from the star, contrary to recent findings for O star winds. Using empirical mass-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 17 publications
7
25
0
2
Order By: Relevance
“…There is considerable observational evidence that hot-star winds are clumped both on small and large length scales. The presence of structure significantly influences the mass-loss rate determinations ( Fullerton et al 2006;Prinja et al 2005;Puls et al 2006). This in turn is important for models of stellar and galactic evolution.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable observational evidence that hot-star winds are clumped both on small and large length scales. The presence of structure significantly influences the mass-loss rate determinations ( Fullerton et al 2006;Prinja et al 2005;Puls et al 2006). This in turn is important for models of stellar and galactic evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Prinja et al 2005) and Si 3+ may be expected to be dominant. However, the spectra of both stars have Si iiiλ1206 and C ivλλ1550 wind lines that are unsaturated at intermediate velocities and have saturated NACs.…”
Section: Discussionmentioning
confidence: 99%
“…The surveys cited above suggest that NACs may be present, at some time, in most OB stars with well developed but unsaturated wind lines. For example, a preliminary examination of the 106 B0-B5 supergiant sample analysed by Prinja et al (2005) indicates that NACs are evident in ∼70% of the stars which exhibit well-developed, unsaturated P Cygni profiles in either Siiv or Civ.…”
Section: Narrow Absorption Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameters of the calculated m-CAK models with δ 0 from Abbott (1982), terminal velocity, V ∞ (km s −1 ), the local mass loss rate, F m (10 −6 M yr −1 ) and r c /R * , the location of the critical point. Prinja et al (2005) investigated the ionization structure of early-B supergiant winds and demonstrated that the wind ionization increases with distance from the star. This structure is different to the one exhibited by an O-star wind.…”
Section: The Slow Solutionmentioning
confidence: 99%